2019
DOI: 10.18280/acsm.430411
|View full text |Cite
|
Sign up to set email alerts
|

Electro Thermal Modelling of Electrical Discharge Machining of Be-Cu Alloy by Varying Fraction of Energy

Abstract: Beryllium Copper (Be-Cu) alloy are advanced engineering alloy bearing high strength, high wear resistance, Corrosion resistance and nonmagnetic nature. These properties of Beryllium copper make it impossible to machining through Conventional machining process. Electrical Discharge machining (EDM) is a revolution to machine any type of harder material (Electrically conductive) without any physical pressure. EDM is best suitable to machine Be-Cu alloy for small holes and intricate shape used in heat exchanger. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The adverse effect of discharge energy also provided some insights on the fatigue strength of the workpiece that propagates from the multiple surface imperfections within this white recast layer. The tensile residual stresses and the recast layer thickness and forming of the cracks with larger sizes on this recast white layer increase the generated heat energy per unit spark [14]. The machined samples of the AISI D2 die steel workpieces having an external melting layer (white layer), the heat-affected zones (HAZ), and the tempered layer macro-metallographic after the EDM processes using graphite and copper tools electrodes.…”
Section: Materials Science and Modern Manufacturingmentioning
confidence: 99%
See 1 more Smart Citation
“…The adverse effect of discharge energy also provided some insights on the fatigue strength of the workpiece that propagates from the multiple surface imperfections within this white recast layer. The tensile residual stresses and the recast layer thickness and forming of the cracks with larger sizes on this recast white layer increase the generated heat energy per unit spark [14]. The machined samples of the AISI D2 die steel workpieces having an external melting layer (white layer), the heat-affected zones (HAZ), and the tempered layer macro-metallographic after the EDM processes using graphite and copper tools electrodes.…”
Section: Materials Science and Modern Manufacturingmentioning
confidence: 99%
“…It is an electro-thermal process in which the electrical energy is converted to highly energize thermal energy that helps erode the material from the workpiece by a series of electric sparks. The arc was initiated between the electrode tool and the workpiece [14].…”
Section: Introductionmentioning
confidence: 99%
“…As a conclusion, he demonstrated that the model established by DiBitonto et al [1] has the strongest agreement with experimental data. Recently published papers (Shuvra Das et al [3]; Kansal et al [17]; Marafona and Chousal [18]; Ghanem et al [19]; Salah, N.B et al [20,21]; Bhondwe et al [22];…”
Section: Introductionmentioning
confidence: 99%
“…Marafona and Chousal [18] assume that the fraction of energy transmitted to the workpiece is 50%. According to Kansal et al [17] and Bhondwe et al [22], the powder fraction (Fc) is dependent on the dielectric fluid used.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, a significant amount of improvements in their structures can be achieved due to which it can be used in some functional applications in place of metal and its alloy like biomedical implants, electronic chip, heat exchangers in thermal power plant, wear resistance parts and as various coatings over metal to increase mechanical properties, like their high hardness, chemical inertness and high electrical and thermal insulating properties [3]. This potential ceramic composite has also ability to replace metal and its alloys (Be-Cu alloy) in thermal industry [4]. But at the same time, the above application requires a highly finished surface with dimensionally accurate machined holes.…”
Section: Introductionmentioning
confidence: 99%